Psychological view on students’ conviction in mathematical proof - F Fuat; T Nusantara; E B Irawan; S Irawati (Pascasarjana Universitas Pendidikan Indonesia, 2018)
There are only few mathematics students who feel convinced with their proof construction. The studies about conviction are mainly done psychologically. Students’ conviction in mathematical proof was mostly studied based on their utterances when they were being interviewed. Therefore, the components which cause the conviction were not elaborated clearly. In this study, we found eight psychological components which caused students to feel convinced with their mathematical proof construction. These components were based on students’ disclosure on their proof constructions. Those components were: concrete (conformity of the argument given, in the form of verbal, written and figure presented in proof construction), familiar (fluency in giving reasons to the statement given), detailed (argument is conveyed in a well-detailed manner), generalized (the overall presentation is generalized), clear (the ability to give a good and correct explanation to each statements and the reason of constructing the proof), valid (can give logical reasons to all of the statements in proof constructions in complete and detailed manner), feasible (the statement presented is appropriate or fulfill the proof) and caprice (there are words, gestures, and attitudes that indicate a doubt).